Contribution of the lower extremity joints to mechanical energy in running vertical jumps and running long jumps - Stefanyshyn, D. J.; Nigg, B. M. (Journal of Sports Sciences, 1998)
The energy contribution of the lower extremity joints to vertical jumping and long jumping from a standing position has previously been investigated. However, the resultant joint moment contributions to vertical and long jumps performed with a running approach are unknown. Also, the contribution of the metatarsophalangeal joint to these activities has not been investigated. The objective of this study was to determine the mechanical energy contributions of the hip, knee, ankle and metatarsophalangeal joints to running long jumps and running vertical jumps. A sagittal plane analysis was performed on five male university basketball players while performing running vertical jumps and four male long jumpers while performing running long jumps. The resultant joint moment and power patterns at the ankle, knee and hip were similar to those reported in the literature for standing jumps. It appears that the movement pattern of the jumps is not influenced by an increase in horizontal velocity before take-off. The metatarsophalangeal joint was a large energy absorber and generated only a minimal amount of energy at take-off. The ankle joint was the largest energy generator and absorber for both jumps; however, it played a smaller relative role during long jumping as the energy contribution of the hip increased.